Vocalization Repertoire of the Five Striped Palm Squirrel, Funambulus pennantii pennantii: An Ethological Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The five striped palm squirrel, Funambulus pennantii pennantii is native to Northern India, Iran, Pakistan and Bangladesh. The vocal communication of F. p. pennantii was studied at four different sites at Agra district of Uttar Pradesh, India. These sites were selected on the basis of maximum cluster locations and movements of squirrels tracked by the GPS tracking device GARMIN eTrex 10. The locations data was uploaded on QGIS open access software to map the sites. To record the vocalizations of squirrels, the AE mini digital recording device was used. Since this species enjoys the Least Concern (LC) status, Godden’s formula for infinite population was employed to determine the sample size, which was approximately 400 squirrels. To generate the audio spectrograms of squirrel vocalizations, MATLAB software version R2019b was used. Photography and videography were done through ad libitum sampling technique with NIKON COOLPIX 500 camera. Four distinct patterns emerged in the audio spectrograms, and they were identified as four distinct call types. The Buzz is a mating and play call. It is also used by mothers to communicate with their juveniles. The Growl is a threat call and is followed by chase or attack. The Bark is an alarm call which is of two types- a predator class specific alarm call for aerial predators and another predator class specific alarm call for terrestrial predators. The Rattle is a territorial declaration by squirrels as their routine at a specific time of a day. This is the first report of acoustic identification and analysis of calls of F. p. pennantii in their behavioral contexts.